Liquidity, Leverage, and Company Size on Earnings Quality with Profitability as a Moderating Variable - Pratama, Sandyka David Yudha; Alfatihah , Najwa; Audistya , Syevina; Neliana, Tri (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The aim of this research is to test and analyze the influence of liquidity, leverage and company size on earnings quality using profitability as a moderating variable. Design/methodology/approach: The population in this study are transportation companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique using purposive sampling technique resulted in 51 company observations. The analysis techniques used are Descriptive Statistical Analysis and Moderated Regression Analysis (MRA) as moderated regression analysis. The data analysis technique uses IBM SPSS Statistics 25 software.). Research Findings: The results of hypothesis testing show that liquidity and leverage have an effect on earnings quality, while company size has no effect on earnings quality. Profitability moderates the influence of leverage and company size on earnings quality, but is unable to moderate the positive influence of liquidity on earnings quality. Theoretical Contribution/Originality: The findings of this study may also have implications for further research and policy-making related to financial disclosure and corporate regulation. Keywords: Liquidity, leverage , company size, profitability, earnings quality